Low fermentable oligosaccharides, disaccharides, monosaccharides, and polyols diet in children - Fodor, Ioana (World J Clin Cases, 2019)
Irritable bowel syndrome (IBS) is a lifelong condition with a high prevalence among children and adults. As the diet is a frequent factor that triggers the symptoms, it has been assumed that by avoiding the consumption of fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP), the symptoms might be improved. Therefore, in the past decade, low FODMAP diet has been intensively investigated in the management of IBS. The capacity of FODMAPs to trigger the symptoms in patients with IBS was related to the stimulation of mechanoreceptors in the small and large intestine. This stimulation appears as a response to a combination of increased luminal water (the osmotic effect) and the release of gases (carbon dioxide and hydrogen) due to the fermentation of oligosaccharides and malabsorption of fructose, lactose and polyols. Numerous studies have been published regarding the efficacy of a low FODMAP diet compared to a traditional diet in releasing the IBS symptoms in adults, but there are only a few studies in the juvenile population. The aim of this review is to analyze the current data on both low FODMAP diet in children with IBS and the effects on their nutritional status and physiological development, given the fact that it is a restrictive diet.